(untitled) (Archive of Conferences, 2021)
Autogenerators are sources of primary vibrations. They apply in all radio engineering systems as exciters of transmitters, sources reference, reference signals and are the most critical elements [1]. Dynamic chaos is a complex, disordered movement of nonlinear systems, arising in the absence of any random disturbances - since 1992 attracts increased attention due to the steady trend of transition from theory to practice.